Epistemic tools for science classrooms: The continual need to accommodate and adapt. Issue 4 (25th March 2019) - Settlage, John; Southerland, Sherry A.
Abstract: Epistemic tool implementation in science classrooms builds on the practice turn unique to the current era of science education reform. In this essay, we consider how professional science engage with objects that serve epistemic goals. We also consider the challenge of adapting epistemic tools to a variety of science learning contexts.